Maintaining Customer Loyalty: Analysis of Factors that Influencing Customer Loyalty to Local Beauty Mask - Yuwono, Wisnu; Naimah, Mutiara Kamilatu; Yulianto, Edy (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The aim of this research is to identify the effects of customer experience, customer value, price, product quality, and service quality on customer loyalty through customer satisfaction. A quantitative survey methodology was employed, with 405 participants as survey respondents. In this study, we utilized SPSS version 26 for descriptive analysis and employed Partial Least Squares (PLS) to test causal relationships and assess the overall influence of each variable. Findings indicate that customer experience, customer value, product quality, and service quality positively or significantly influence customer loyalty, while price does not impact customer loyalty. Customer satisfaction is highly influenced by the quality of service provided, and customers tend to be more satisfied after regaining trust in the company. Customer satisfaction acts as a positive mediator between customer experience and customer loyalty. Customer satisfaction refers to the overall evaluation of the customer's experience with a product or service and the emotions generated from that experience. When customers are satisfied with their experience, they are likely to have positive emotions and remain loyal to the company.